2008
DOI: 10.1001/archsurg.143.6.558
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thyroid Gland Volume in Preoperative Detection of Suspected Malignant Thyroid Nodules in a Multinodular Goiter

Abstract: The detection of suspected malignant thyroid nodules by ultrasonography is associated with thyroid gland volume and tumor size. Design: Prospective clinical trial. Setting: A tertiary referral center. Patients: Three hundred sixty-five patients with a multinodular goiter with coexistent dominant nodules. Main Outcome Measures: The correlation between thyroid gland volume and tumor size and the detection of suspected malignant thyroid nodules by ultrasonography. The incidence of thyroid carcinoma inside and out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
1
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 38 publications
2
13
1
4
Order By: Relevance
“…Our results are confirmed by work performed by Erbil et al 2 who showed a positive correlation between a smaller thyroid volume and a higher detection rate of suspected malignant thyroid nodules in patients with MNG. They found that thyroid gland volumes less than 38 ml had a 48-fold increase in the rate of detecting suspected thyroid cancer.…”
Section: Discussionsupporting
confidence: 91%
“…Our results are confirmed by work performed by Erbil et al 2 who showed a positive correlation between a smaller thyroid volume and a higher detection rate of suspected malignant thyroid nodules in patients with MNG. They found that thyroid gland volumes less than 38 ml had a 48-fold increase in the rate of detecting suspected thyroid cancer.…”
Section: Discussionsupporting
confidence: 91%
“…7 Also Erbil et al reported in a population of 402 patients, that the thyroid volume in patients with thyroid carcinoma was 38 ± 18 mL and in patients with benign diseases it was 73.3 ± 48 mL. 8 The mean thyroid volume of our study group was 26.38 ± 14 mL, which is higher than the healthy population but still lower than Erbil's results. These findings may explain the fact that in our study this volume did not have any effect on intubation condition.…”
Section: Discussioncontrasting
confidence: 52%
“…More recently, ultrasound compressibility or elastography has been shown to distinguish between benign and malignant nodules in which significantly higher stiffness or less compressibility of thyroid lesions correlates highly with malignancy [14 ]. Additionally, smaller thyroid gland volume less than 38 ml and malignant thyroid nodule size of greater than 0.7 cm measured by ultrasound are associated with a 48-fold increased rate of malignancy [15].…”
Section: Characteristics Of Thyroid Nodulesmentioning
confidence: 99%